Joy in Service on Rue Tagore - Muldoon, Paul (New York : Farrar, Straus and Giroux, 2024)
"A new collection of poetry by the Pulitzer Prize-winning poet Paul Muldoon"--.
new book winter 2025.
Keywords: Poetry; POETRY / English, Irish, Scottish, Welsh; European Union countries; Poetry